Developing CapCut-Based Video Tutorials for Learning Outcomes in Creative Product and Entrepreneurship - Lenita Eka Mayasari; Nur Qudus; Ade Novi Nurul Ihsani; Sri Endah Wahyuningsih (Journal of Vocational and Career Education, 2024)
This research is motivated by the absence of video tutorial-based learning media for creating headpieces in the Creative Product and Entrepreneurship course. The printed modules and YouTube links provided by teachers have not effectively enhanced students understanding. Therefore, this study aims to: 1) develop CapCut-based video tutorial learning media, 2) analyze the feasibility of CapCut-based video tutorial learning media, 3) analyze the differences in student learning outcomes after implementing the media, and 4) evaluate the effectiveness of CapCut-based video tutorial learning media on students learning achievements. This research employs the Borg and Gall development model with 10 stages. The study subjects consist of 69 students from the Beauty and SPA vocational program. The analysis focuses on CapCut video tutorials for creating floral themed fantasy headpieces using plastic waste. The instruments used include observation sheets, questionnaires, and tests. The results indicate that CapCut-based video tutorial media are user-friendly, engaging, and capable of increasing student learning motivation. Based on evaluations by media and subject matter experts, the media are considered highly feasible. The independent sample t-test results reveal a significant difference in students learning outcomes before and after using the CapCut-based video tutorials. The average N-Gain was 87.4% in the experimental class and 24% in the control class, demonstrating the effectiveness of this learning media in improving student learning outcomes